Human Umbilical Cord Mesenchymal Stem Cell-induced Osterix, Bone Morphogenetic Protein-2, and Tartrate-resistant Acid Phosphatase Expression in Osteoporotic Mandibular Bone - Hendrijantini, Nike; Hartono, Cindy Karina; Daniati, Reni Puspa; Hong, Guang; Sitalaksmi, Ratri Maya; Kuntjoro, Mefina; Ari, Muhammad Dimas Aditya (European Journal of Dentistry, 2020)
Objectives The aim of this study was to prove that human umbilical cord mesenchymal stem cell (hUCMSC) therapy conducted according to the mandibular osteoporotic model will increase Osterix (Osx) and bone morphogenetic protein-2 (BMP-2) expression, while reducing tartrate-resistant acid phosphatase (TRAP) expression. PKH26 labeling proves that mandibular bone regeneration is produced by hUCMSCs induction.Materials and Methods This study incorporated a true posttest only control group design. Twenty-five female Wistar rats were randomly divided into five groups consisting of the sham surgery (N) group, osteoporotic groups injected with gelatin for 4 weeks (G4) and 8 weeks (G8), and osteoporotic groups injected with hUCMSC-gelatin for 4weeks (SC4) and 8 weeks (SC8). All subjects were provided for BMP-2, Osx, and TRAP on immunohistochemistry examination and PKH-26 labeling.Statistical Analysis All data were analyzed using ANOVA and Tukey HSD tests with p < 0.05 being considered as statistically significant.Results Compared with other groups, the highest level of BMP-2 and Osx occurred in the sham surgery (N) and osteoporotic groups injected with hUCMSCs-gelatin (SC), while the lowest level of TRAP was found in SC4. During 4- and 8-week observation periods, the PKH 26 appeared green (fluorescent).Conclusions hUCMSC demonstrates high-osteogenic activity and increased osteoporotic mandibular bone regeneration, as shown by increased expression of Osx and BMP-2 and decreased TRAP expression. From the labeling, PKH-26 proved that viable hUCMSCs in gelatin solvent can be present in the mandibular bone and be capable of promoting osteogenic differentiation and increasing mineralization and bone formation in the osteoporotic mandibular bone.
Keywords: stem cells; osteoporosis; bone; BMP 2; osterix; TRAP; PKH-26